Liquid-Liquid Phase Behavior of Solutions of 1-Hexyl-3-methylimidazolium Bis((trifluoromethyl)sulfonyl)amide (C(6)mimNTf(2)) in n-Alkyl Alcohols - Vale, Vlad R.; Rathke, Bernd; Will, Stefan; Schröer, Wolfram (Journal of Chemical and Engineering Data, 2011)
Liquid-liquid phase diagrams of binary mixtures of the ionic liquid 1-hexyl-3-methylimidazolium bis((trifluoromethyl)sulfonyl)amide (C(6)mimNTf(2)) with n-alkyl alcohols (hexan-1-ol, heptan-1-ol, octan-1-ol, nonan-1-ol, decan-1-ol, undecan-1-ol, dodecan-1-ol, and tetradecan-1-ol) are reported. By application of the cloud-point method on a set of samples, phase diagrams were obtained at atmospheric pressure over the temperature range (280 to 423) K. The investigated systems show partial miscibility with an upper critical solution temperature (UCST) between (306 and 401) K With increasing chain length of the alcohol, the UCST shifts toward higher temperatures and slightly higher concentrations. Ising criticality was assumed in the numerical analysis of the phase diagrams. The analysis yielded the UCST, the corresponding critical composition, and the width and diameter parameters that characterize the shape of the phase diagrams. The temperature dependence of the diameter of the phase diagram, which determines the asymmetry of the phase diagram, is not linear as presumed by the rectilinear diameter rule of Cailletet-Mathias. Instead, as requested by the theory of complete scaling, it also depends on nonlinear, nonanalytical contributions that are the leading terms when the critical solution point is approached. The shapes of the phase diagrams of the investigated solutions are very similar when the data are represented in terms of corresponding-states variables.